2007
DOI: 10.1590/s1413-294x2007000100010
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à depressão relacionada ao trabalho de enfermagem

Abstract: A depressão, problema enfrentado pelos profissionais de enfermagem, pode acarretar absenteísmo no trabalho. Este estudo teve por objetivo identificar evidências científicas sobre a ocorrência de depressão relacionada ao trabalho de enfermagem e caracterizar fatores desencadeantes e estratégias utilizadas para a prevenção da doença. Revisamos a literatura por meio de levantamento das pesquisas publicadas entre 1995-2005, em revistas indexadas nas bases nacionais e internacionais. Constatou-se que a saúde mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
25

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 10 publications
1
11
1
25
Order By: Relevance
“…Depression is one of the illnesses that most affects these professionals, causing damage to their work capacity and personal lives (1,(5)(6)10,(13)(14) . Because the state of depression is a predictor for increased risk of suicide (17,22) , nursing professionals exhibit higher risk for suicide (5) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Depression is one of the illnesses that most affects these professionals, causing damage to their work capacity and personal lives (1,(5)(6)10,(13)(14) . Because the state of depression is a predictor for increased risk of suicide (17,22) , nursing professionals exhibit higher risk for suicide (5) .…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that depression in nurses was also associated with insecurity in developing their work activities, which are characterized by high expectation standards, especially when they are highly complex or involve the possibility of patient death (14,22) . At times, psychological distress has contributed to coping with professional demands through the desire to escape from responsibilities with passivity and pessimism, common in depression (14) .…”
Section: Insecurity In Developing Activitiesmentioning
confidence: 99%
See 3 more Smart Citations